The effects of case management for breast cancer patients: A protocol for systematic review and meta-analysis. Issue 9 (4th March 2022) - Chai, Yong; Li, Li; Wu, Yun-Lian; Wang, Tao; Jia, Yu-Ming; Lin, Xiao-Li; Chen, Xi; Zhong, Hui; Liu, Li-Xia; Tao, Lian-De
Abstract: Background: Female breast cancer is the most common cancer nowadays, and its treatment has a significant impact on patients both physically and psychologically. Many randomized trials have proved that case management (CM) can effectively care for patients. However, there is a lack of systematic scientific evaluation, so this systematic evaluation aims to explore the impact of CM on breast cancer patients. Methods: PubMed, Embase, Cochrane Library, Scopus, CINAHL were searched. Chinese repositories included China National Knowledge, Infrastructure Database (CNKI), Wan fang Database, China Biology Medicine Database. We will also search unpublished literature at ClinicalTrials.gov. Randomized controlled trials were collected from them. The literature will be screened according to inclusion and exclusion criteria, and 2 researchers will extract the literature independently. The primary outcome indicator for this study will be patient satisfaction. Statistics were performed using RevMan 5.4 software. The quality of each outcome will be evaluated using the Grading of Recommendations Assessment, Development, and Evaluation. Results: This study will provide the most recent evidence for evaluating the impact of CM on breast cancer patients. Conclusion: To evaluate the impact of CM on patients with breast cancer. Registration number: DOI:10.17605/OSF.IO/ZJKHX.